Quality assurance practices in software testing / Normawarzura Mat Desa - Mat Desa, Normawarzura (2004)
The process of achieving quality today is complex. The cotemporary ideas of achieving quality always update. So do how quality is being practiced. Therefore, the practitioners of quality still remain transparent to most organizations. This research is intended to identify the Quality Assurance practice in software testing and examine the possible issue and barriers due the implementation. The qualitative methodology has been adopted in the research of the findings, hiterviews were conducted with associated person who is involved in software development particularly in software testing. The data were collected, analyzed and presented as discussion and finding of this research. Later in this report, conclusion and recommendation made from discussion and finding in order to achieve the objective of the research.